Effect of exogenously administered glucagon versus spontaneous endogenous counter‐regulation on glycaemic recovery from insulin‐induced hypoglycaemia in patients with type 2 diabetes treated with a novel glucokinase activator, AZD1656, and metformin. Issue 11 (3rd July 2014) - Krentz, A. J.; Morrow, L.; Petersson, M.; Norjavaara, E.; Hompesch, M.
<x xml:space="preserve">Abstract</x> Aims To study the effect of exogenous i.m. glucagon on recovery from controlled insulin‐induced hypoglycaemia in patients with type 2 diabetes treated with the novel glucokinase activator AZD1656, in combination with metformin. Methods This was a single‐centre randomized, open, two‐way crossover phase I, automated glucose clamp (Biostator®; Life Science Instruments, Elkhart, MD, USA) study (NCT00817271) in eight patients (seven men and one woman, mean age 58.6 years, body mass index 28.1 kg/m2). All patients received a stable dose of metformin twice daily, ranging from 1000 to 2250 mg. A 2‐day titration phase commenced with 40 mg AZD1656 twice daily, escalating to 80 mg twice daily if tolerated. This was followed by a single dose of 80 or 160 mg AZD1656, administered on days 5 and 8 when metabolic studies were performed. After an overnight fast on days 5 and 8, controlled hypoglycaemia was induced using an exogenous i.v. infusion of insulin. Plasma glucose was lowered in a stepwise fashion over 3 h to attain a target nadir of 2.7 mmol/l. This was sustained for 30 min, at the end of which the hypoglycaemic clamp was released. In random sequence, patients either received an i.m. injection of 1 mg glucagon or were allowed to recover from hypoglycaemia by endogenous counter‐regulation. To avoid prolonged hypoglycaemia, a reverse glucose clamp was applied from 4 to 6 h post‐dose. Results Three patients received 40 mg AZD1656 twice daily and five patients 80 mg twice daily. Mean plasma glucose at 20 min after release of the hypoglycaemic clamp was significantly lower (3.1 ± 0.3 mmol/l) for AZD1656 alone than for AZD1656 + glucagon (4.9 ± 0.8 mmol/l; p < 0.001 between the groups). Catecholamine and cortisol responses were similar on the AZD1656 + glucagon and AZD alone study days. Growth hormone response was 18% lower for AZD1656 alone (p = 0.01), consistent with the effect of a pharmacological dose of glucagon on growth hormone secretion. No safety or tolerability concerns were observed during treatment with AZ1656. Conclusions Exogenous glucagon was effective as a rescue treatment for hypoglycaemia induced during treatment with AZD1656, given in combination with metformin in patients with type 2 diabetes.